2020
DOI: 10.1002/smtd.201900826
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Self‐Supported Catalysts for CO2 Electrochemical Reduction

Abstract: Electrochemical reduction of CO2 may provide a promising method to mitigate the concentration of CO2 in the atmosphere, and simultaneously convert this greenhouse gas into value‐added fuels or chemicals. However, electrocatalysts for CO2 reduction are mostly powder based; therefore, polymer binders are always employed to make these catalysts useful as working electrodes. As a consequence, plenty of active sites are embedded inside without catalytic performance, causing a relatively low efficiency. On the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 108 publications
0
37
0
Order By: Relevance
“…Conversion of CO 2 to value‐added chemicals could help reduce the atmospheric CO 2 concentration and alleviate the dependence on fossil fuels. Using electricity generated from renewable energy sources, CO 2 can be electrochemically reduced to energy‐rich products such as carbon monoxide (CO), which is one of the most important feedstock to be used in the Fischer–Tropsch industrial process [1–5] . Over the past decades, various electrode materials for the conversion of CO 2 ‐to‐CO have been explored, such as Au, Ag, Cu metals, [6–9] metal complexes [10–13] and single‐atom Fe, Co, Ni based catalysts, [14–30] metal‐free carbons [31–33] .…”
Section: Introductionmentioning
confidence: 99%
“…Conversion of CO 2 to value‐added chemicals could help reduce the atmospheric CO 2 concentration and alleviate the dependence on fossil fuels. Using electricity generated from renewable energy sources, CO 2 can be electrochemically reduced to energy‐rich products such as carbon monoxide (CO), which is one of the most important feedstock to be used in the Fischer–Tropsch industrial process [1–5] . Over the past decades, various electrode materials for the conversion of CO 2 ‐to‐CO have been explored, such as Au, Ag, Cu metals, [6–9] metal complexes [10–13] and single‐atom Fe, Co, Ni based catalysts, [14–30] metal‐free carbons [31–33] .…”
Section: Introductionmentioning
confidence: 99%
“…Conversion of CO 2 to value-added chemicals could help reduce the atmospheric CO 2 concentration and alleviate the dependence on fossil fuels.U sing electricity generated from renewable energy sources,C O 2 can be electrochemically reduced to energy-rich products such as carbon monoxide (CO), which is one of the most important feedstock to be used in the Fischer-Tropsch industrial process. [1][2][3][4][5] Over the past decades,v arious electrode materials for the conversion of CO 2 -to-CO have been explored, such as Au,A g, Cu metals, [6][7][8][9] metal complexes [10][11][12][13] and single-atom Fe,C o, Ni based catalysts, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] metal-free carbons. [31][32][33] Nevertheless,i t still remains several challenges for the CO 2 electroreduction reaction (CO 2 RR), including low energy conversion efficiency,p oor selectivity and stability.T herefore,i ts till needs design and fabrication of highly active,s elective and robust electrocatalysts towards CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%
“…Most working electrodes are electrodes with catalysts supported on a substrate, such as gas diffusion electrodes on carbon paper, membrane electrode assembly, and self‐supported electrodes. [ 46,226 ] The former two electrodes are usually fabricated from powder catalysts, while the latter one typically uses catalysts supported on themselves or the derived integrated electrodes (e.g., Cu foil, Cu foam, and carbon arrays) as the electrodes. It was found that the stereospecificity and hydrophilicity/hydrophobicity are two key factors in modulating the catalytic performance (e.g., activity and selectivity) of CO 2 RR electrodes.…”
Section: Cell Engineeringmentioning
confidence: 99%